The exploration of political conflicts and personal relationships in Ian McEwan's The Innocent - Abbasiyannejad, Mina; Talif, Rosli (SAGE Publications, 2014)
Political conflicts have historically affected the relationships of nations. Ian McEwan’s The Innocent is an excellent example of a story set within the web of such a conflict—the Cold War—that was brought about by U.S. and Soviet confrontation over spheres of influence after the Second World War. This article aims to show how Ian McEwan pictures Americanization as a form of cultural politics aimed at spreading American influence throughout the occupied countries such as Germany for political domination. Max Weber’s theory of political power along with semiotics as a tool is the framework of the article. Signs that refer to the Americanization process, including inferences in the dialogues, gestures, choice of food, and even clothing, are scrutinized and interpreted within the socio-political context the of Cold War. The analysis of The Innocent provides an example of the ways in which fiction represents political conflicts permeating personal and intimate relationships, and how such conflicts may result in a sense of mistrust and intrigue among both people and nations.